2017
DOI: 10.18632/oncotarget.16575
|View full text |Cite
|
Sign up to set email alerts
|

Elevated heparanase expression is associated with poor prognosis in breast cancer: a study based on systematic review and TCGA data

Abstract: Heparanase promotes tumorigenesis, angiogenesis, and metastasis. Here, we conducted a study based on systematic review and the Cancer Genome Atlas (TCGA) data that examined heparanase expression in clinical samples to determine its prognostic value. According to the meta-analysis and TCGA data, we found that heparanase expression was up-regulated in most breast cancer specimens, and elevated heparanase expression was associated with increased lymph node metastasis, larger tumor size, higher histological grade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The same principles are also relevant to breast cancer. Heparanase is undetected in normal breast epithelium but its expression is induced in human breast carcinoma, associated with increased tumor metastasis and larger tumor size [ 15 17 ]. Similarly, overexpression of heparanase promotes, while anti-heparanase siRNA decreases the growth, angiogenesis, and metastasis of breast carcinoma cells [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same principles are also relevant to breast cancer. Heparanase is undetected in normal breast epithelium but its expression is induced in human breast carcinoma, associated with increased tumor metastasis and larger tumor size [ 15 17 ]. Similarly, overexpression of heparanase promotes, while anti-heparanase siRNA decreases the growth, angiogenesis, and metastasis of breast carcinoma cells [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, overexpression of heparanase promotes, while anti-heparanase siRNA decreases the growth, angiogenesis, and metastasis of breast carcinoma cells [ 18 20 ]. In addition, heparanase inhibitors were found to efficiently attenuate the tumorigenic capacity of breast carcinoma cells [ 21 , 22 ], altogether implying that heparanase plays a decisive role in breast cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We then investigated the mechanism underlying the differences in cell clusters formation in the various cell lines. Heparanase is an endoglycosidase that up-regulated in breast cancer and associated with elevated metastasis, advanced histological grade, and poor survival [21] . We hence detected heparanase expression in these cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…HPSE expression strongly correlates with poor survival in BC (Sun, Zhang et al 2017) and serum levels of shed SDC1 have been identified to be informative in regards to progression of several cancers including breast (Joensuu, Anttonen et al 2002, Vassilakopoulos, Kyrtsonis et al 2005, Szarvas, Reis et al 2016. Shed SDC1 abundance detected in serum has been associated with BC size (Malek-Hosseini, Jelodar et al 2017), and to be a result of chemotherapy (Ramani and Sanderson 2014).…”
Section: Introductionmentioning
confidence: 99%